If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49 = 6x + 1 Reorder the terms: 49 = 1 + 6x Solving 49 = 1 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 49 + -6x = 1 + 6x + -6x Combine like terms: 6x + -6x = 0 49 + -6x = 1 + 0 49 + -6x = 1 Add '-49' to each side of the equation. 49 + -49 + -6x = 1 + -49 Combine like terms: 49 + -49 = 0 0 + -6x = 1 + -49 -6x = 1 + -49 Combine like terms: 1 + -49 = -48 -6x = -48 Divide each side by '-6'. x = 8 Simplifying x = 8
| 16=10b | | 8x+15=12x+3 | | 5y+6=2y+9 | | 39+6x+6=x^2+2x | | z=X-51/8 | | -11(-9)= | | 3a+2[2+39a-1]=2(3a+4) | | z=41-51/8 | | Log(8)x+2log(8)2=2 | | Log(8)+2log(8)2=2 | | -6-4x=6(1-7x)+4x | | x^2-4x+4+56=x^2 | | 35-3v=4v | | 43=4x+3 | | 6(6x-1)+4x=5x+50 | | q+7=8q+14 | | a(4a-15)=25 | | .45x+.05(14-x)=.10(71) | | 49x^2+28x+2=0 | | 2+-2=20 | | 10a=6a+36 | | x^4=x^4-8x^3+24x^2-32x+56+6 | | 4(-5)+(-5)+8=-32-3(-5) | | x^4=x^4-8x^3+24x^2-32x+56 | | -28a+21=-35 | | 15954a+1690b+1043c=127830000 | | a+b+c=25900 | | 36-9r=r*r | | 2n-1=8191 | | =6.5-0.83t | | 64=.5(x^2+8x) | | 7-6x=7+5x+5x |